1998
DOI: 10.1038/sj.ijo.0800552
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that eating frequency is inversely related to body weight status in male, but not female, non-obese adults reporting valid dietary intakes

Abstract: OBJECTIVE: To investigate the relationships between eating frequency (EF) and body weight status and to determine whether these relationships can be explained in terms of differences in physical activity levels, macronutrient intakes or energy compensation. DESIGN: Cross-sectional design; free-living subjects, 48 men and 47 women (aged 20±55 y, body mass index (BMI) 18±30), recruited in a workplace setting. MEASUREMENTS: Height and weight; skinfold thickness (four sites); EF, energy and macronutrient intakes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
155
3
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(169 citation statements)
references
References 35 publications
9
155
3
2
Order By: Relevance
“…10,11,[57][58][59][60][61][62][63] Also contrary to previous reports showing breakfast skipping, reduced energy intake at breakfast and/or increased energy intake later in the day being associated with a higher BMI or energy intake, 11,12,14,64 we found no such relationships. Instead, total energy intake, or energy at all meals and snacks rather than any particular eating occasion, was associated with a higher BMI in both age groups.…”
Section: Discussioncontrasting
confidence: 99%
“…10,11,[57][58][59][60][61][62][63] Also contrary to previous reports showing breakfast skipping, reduced energy intake at breakfast and/or increased energy intake later in the day being associated with a higher BMI or energy intake, 11,12,14,64 we found no such relationships. Instead, total energy intake, or energy at all meals and snacks rather than any particular eating occasion, was associated with a higher BMI in both age groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, a very limited number of studies (16,17,19,20) , but not all (1,3,6,10,12,13) , suggest that EF is positively, rather than inversely, associated with adiposity measures after accounting for EI reporting bias. Third, interpreting the literature on EF is complicated by the fact that there is no consensus about what constitutes a snack, a meal or an eating occasion.…”
mentioning
confidence: 99%
“…Third, interpreting the literature on EF is complicated by the fact that there is no consensus about what constitutes a snack, a meal or an eating occasion. While some researchers have relied on respondents' self-identification of meals, snacks or eating occasions (2,(5)(6)(7)(11)(12)(13)(14)(15)18) , others have attempted to use more objective criteria (1,3,4,(8)(9)(10)16,17,19,20) . As a consequence of these methodological limitations, the discrepant findings are not surprising, and severely impede clarification of the impact of EF on diet quality and adiposity status.…”
mentioning
confidence: 99%
“…Eating occasions were defined as any occasion when any food or drink was consumed (24)(25)(26)30) . In many previous studies, if two eating occasions occurred in ≤15 min, both events were counted as a single eating occasion; when >15 min separated two eating occasions, these were considered distinct eating occasions (20,21,23,24,30) . In the present study, however, all foods and beverages reported at one discrete clock time were considered as part of one eating occasion, because almost all eating episodes (>99·5 %) occurred at least 15 min apart in NHANES (44) .…”
Section: Assessment Of Diet Qualitymentioning
confidence: 99%
“…First, EF has often been estimated using a series of self-report questions (8)(9)(10)(11)(15)(16)(17)(18)(19) , the validity of which has not been examined or reported. Only a limited number of studies have estimated EF with the use of information on actual dietary behaviours (based on dietary record or 24 h recall) (20)(21)(22)(23)(24) . Second, there is no consensus about what constitutes a snack, a meal or an eating occasion.…”
mentioning
confidence: 99%